PENGEMBANGAN MEDIA PEMBELAJARAN MENGGUNAKAN APLIKASI BOOK CREATOR BERBASIS PROBLEM BASED LEARNING PADA PEMBELAJARAN IPAS DIKELAS IV SD - Dina Mulyani; Yeni Erita; Hamimah; Leni Zahara (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2025)
This research is motivated by the importance of innovation in learning at the elementary school level to improve the quality of learning. This study aims to produce valid, practical, and effective learning media using the Book Creator application in learning Natural and Social Sciences in grade IV of Elementary School. The type of research used is Research and Development (R&D) with the ADDIE development model (analysis, design, development, implementation, and evaluation). The subjects of the study were teachers and students of grade IV of SDN 28 Air Tawar Timur, 16 Air Tawar Timur, 18 Air Tawar Selatan, and 05 Air Tawar Barat. Data collection techniques were observation and interviews. The research instrument used validity, practicality, and effectiveness tests. The development of learning media obtained a validity result of 92% with a valid category. The practicality results obtained a score of 92.15% by teachers and a score of 93,59% by students with a practical category. Based on the results of the research that has been conducted, it can be concluded that the development of learning media using the Book Creator application has been valid, practical, and effective in learning Natural and Social Sciences in grade IV of Elementary School. The developed learning media can be an alternative solution for innovative and interesting learning media for students in learning teaching materials.